Pengaruh Adopsi Media Sosial terhadap Pertumbuhan UMKM dengan Customer Management Relationship Capabilites sebagai Variabel Mediasi : Studi Kasus UMKM Kota Pasuruan - Zein, Dhani Miftakhul; Akbar, Muhammad Fikri (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of digital transformation and social media utilization on the performance of SMEs, as well as to examine the role of Customer Relationship Management Capability (CRMC) as a mediating variable. A quantitative approach with an explanatory design was employed, with data collected through a structured questionnaire survey administered to 170 SME actors in Pasuruan City. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings reveal that social media adoption does not have a significant effect on SME performance. Conversely, social media adoption has a positive and significant effect on CRMC. Furthermore, social media utilization was found to have a positive and significant effect on SME performance. Finally, CRMC plays a significant mediating role in the relationship between social media adoption and SME performance. Overall, these results highlight the strategic role of social media in strengthening CRM capabilities, which in turn contributes to improving SME performance. The integration of social media technologies with CRMC processes can be regarded as a crucial foundation for building organizational capabilities that are competitive and sustainable.